An investigation into the design for rideability of small wheel single-track bicycles and e-scooters - Paudel, Milan (Nanyang Technological University, 2020)
Over the years, bicycles evolved as one of the most efficient means of transportation. A plethora of bicycles design is available in the market. However, the principal designs and most notably the wheel size has changed little ever since the evolution of the safety bicycles. The bicycles with bigger wheels (26-inch - 29-inch in diameter) have been the most common design and remained dominant over a long period. However, the desire for compact and portable means of transportation led to the invention of the small wheels and small-wheeled personal mobility devices (PMDs) like folding bicycles, kick scooters, e-scooters, Segway and so on. In recent decades, rapid urbanisation has created one of the biggest challenges in the transportation system: the first- and last-mile problem. Today, many modern cities, including Singapore, are restructuring their transport infrastructure to allow greater use of these bicycles and e-scooters to smoothen the first and last mile problem in urban mobility. Small wheel (≤20-inch diameter) bicycles and e-scooters are becoming increasingly popular in such modern cities because of their compactness, manoeuvrability and portability. However, the rideability (i.e. stability and handling) of these small wheelers has often been questioned. It is a well-known fact that the small wheel bicycles and e-scooters do not ride as good as its big wheel counterparts and their ride is often described as “less-stable”, “wobbly” and “twitchy”. Most believed that small wheelers are inherently unstable because of the smaller wheel size. Nonetheless, there has not been any comprehensive investigation to quantitatively compare the performance of the different wheel sized PMDs and suggest possible solutions to improve the current designs of small wheelers. On top of that, the growing popularity and the advent of the micro-mobility in last few years has also brought forth an alarming increase in PMDs related accidents and injuries. Therefore, there is a rising concern about the safety of the riders who use these small wheelers. A comprehensive investigation on the performance of the different wheel sized PMDs is the major objective of this study. The design philosophies, methodologies and available guidelines were analysed for different wheel sized PMDs. The rideability of 20-inch, 16-inch and 12-inch bicycles and 8-inch e-scooters have been studied and compared with that of 26-inch referenced big wheel bicycle based on the dynamic self-stability and handling characteristics. The inherent stability characteristics have been analysed based on the eigenvalues, self-stability velocity range and, the steer and lean oscillation behaviour. Furthermore, the obstacle rollover tendency and steady-state turning performances were considered for handling analysis. Finally, an improved and cost-effective methodology has been established to enhance the performance of small wheel PMDs by incorporating the dynamic models into the design process. Simple front steering design guidelines were developed using the improved design methodology. Prototype small wheel bicycles were fabricated, and their performance was compared analytically and experimentally to the current designs of big and small wheel bicycles. The analysis of current design practice revealed that most of the available design guidelines were developed for big wheel bicycles, and no specific design guidelines were found for designing the small wheelers. Therefore, a strong influence of big wheel bicycles’ design was observed in the designs of small wheel PMDs. Furthermore, the study has successfully confirmed that the current designs of the small wheel PMDs are indeed less stable and difficult to ride at normal speed. The analysis suggested that the available design guidelines for big wheel bicycles do not translate directly to the small wheelers and the performance discrepancy in big wheelers and small wheelers is not because of the smaller wheel sized, as per se but, lack of adequate design guidelines for small wheelers that resulted in lesser stability and poor readability. A good agreement was observed between the experimental and the analytical results for prototype bicycles developed using proposed design guidelines and the current bicycle designs. Therefore, the proposed design guidelines were successfully validated, both analytically and experimentally. Lastly, it has been successfully shown that the current designs of small wheel PMDs are yet to be optimised and performance could be improved by carefully tuning their design configurations such as front steering geometry and mass distribution.